Green Bond, the Financial Instrument that Supports Sustainable Development: Opportunities and Barriers - Mihálovits, Zsolt; Tapaszti, Attila (Public Finance Quarterly, 2018)
Several initiatives have been launched in order to internalize the risks and threats of environmental degradation and climate change. Of these the system of carbon quotas, the spread of green funds and the levying of carbon taxes are the ones that need to be highlighted. Green bonds fit this line. In recent years the market has dynamically developed, but even so these bonds only make up less than 1% of the global bond market. Our article has looked at the barriers to the further expansion of the market and the opportunities for removing these, the uniqueness of environmental threats and the difficulties with their internalization, the possible role of central banks in the development of the green bond market and the arguments for the necessity of global action. Although the widespread adoption of green bonds still awaits, their importance in fostering sustainable growth has by now been widely recognised by both market participants and regulators alike. There have been a great number of initiatives to support market expansion, which may gradually grow into a generally accepted framework that will strengthen the importance of green bonds as a new asset class of its own.